PERAN PENYULUH PERTANIAN DALAM BUDIDAYA PADI SAWAH DI DESA TAWAMELEWE KECAMATAN UEPAI KABUPATEN KONAWE - Sakti Sakti; Musadar Mappasomba; Tjandra Buana (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to ascertain the role of agricultural extension workers in rice cultivation. The population of this study is comprised of all rice farmers residing in Tawamelewe Village, constituting a total sample size of 300 individuals. The sample size was determined using the Slovin formula with a margin of error of 15%, resulting in a sample size of 38 people. The sampling process was executed through the utilization of simple random sampling. The data presented herein was collected through a combination of interviews, documentation, and surveys with questionnaires. The independent variables in this study were the role of agricultural extension workers and rice cultivation. The research data was analyzed using two methods: descriptive analysis and inferential analysis. The results of the study indicate that the role of agricultural extension workers in Tawamelewe Village, Uepai District, Konawe Regency, is in the high category, reflecting that extension workers have performed their functions optimally as facilitators, motivators, innovators, and educators. On the other hand, rice cultivation by farmers in the village is in the good category, indicating that all stages of cultivation, from land preparation to harvest and post-harvest, have been carried out appropriately. Through data analysis using the Sperman Rank test, a correlation coefficient value of 1.000 with a significance level of 0.001 was obtained, indicating a very strong and significant relationship between the role of agricultural extension workers and the success of rice cultivation. The perfect correlation between the role of extension workers and the quality of rice cultivation underscores the importance of optimizing the role of agricultural extension workers as the key to the success of a sustainable cultivation system, and provides a scientific basis for strengthening extension institutions at the village level to enhance overall agricultural productivity.